Morphological and functional characteristics of human spermatozoa after cryopreservation under ultrarapid cooling - Chadaev, V. Ye.; Kuchkov, I. N.; Cherkashina, I. V.; Goltsev, K. A.; Dobrunova, I. V. (Problems of Cryobiology and Cryomedicine, 2005)
Comparative study of key morphological and immunological tests to find functional characteristics of human sperm during cryopreservation under ultrarapid cooling conditions was performed. Freezing regimen was shown to result in re-distribution of the percentage of pathological spermatozoa, by increasing the number of cell forms with a tail damage. There was noted a positive correlation of Kurzrock-Miller and SperMar tests.